2007
DOI: 10.1021/jm7009827
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prodrugs of Tegafur that Display Improved Anticancer Activity and Antiangiogenic Properties

Abstract: New and more potent prodrugs of the 5-fluorouracyl family derived by hydroxymethylation or acyloxymethylation of 5-fluoro-1-(tetrahydro-2-furanyl)-2,4(1H,3H)-pyrimidinedione (tegafur, 1) are described. The anticancer activity of the butyroyloxymethyl-tegafur derivative 3 and not that of tegafur was attenuated by the antioxidant N-acetylcysteine, suggesting that the increased activity of the prodrug is in part mediated by an increase of reactive oxygen species. Compound 3 in an in vitro matrigel assay was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Eight clinically relevant chemotherapeutic agents were tested on their ability to cross the BBB and their cytotoxic effects on glioma cells. The properties of these agents are listed in Supplementary Table 13738394041424344. Among them, only Temozolomide (TMZ) is lipophilic and permeable to BBB, which is used for the treatment of glioblastoma multiforme in clinics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight clinically relevant chemotherapeutic agents were tested on their ability to cross the BBB and their cytotoxic effects on glioma cells. The properties of these agents are listed in Supplementary Table 13738394041424344. Among them, only Temozolomide (TMZ) is lipophilic and permeable to BBB, which is used for the treatment of glioblastoma multiforme in clinics.…”
Section: Resultsmentioning
confidence: 99%
“…Given its solubility, TMZ was dissolved in DMSO, and the other drugs were dissolved in PBS. All eight drugs were prepared at a concentration twice that of their respective IC 50 values3738394041424344. Three groups of experiments were performed: control group (no barrier), BMECs mono-cultured group and BBB group (BMECs co-cultured with astrocytes).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies reported that pure PEI-600 has little cytotoxicity as well as low transfection efficiency (Mintzer and Simanek, 2009), and our approach showed PEI-CyD was a low-toxic carrier in vitro (Tang et al, 2006). Therefore, the enhanced cytotoxicity of PEI-CyD-tegafur might be caused by the elevated bioavailability of tegafur, polymer-mediated efficient delivery (Zhao et al, 2009), amine groups in crosslinked PEI (Tang et al, 2006), and auxiliary formaldehyde-induced antineoplastic activity (Engel et al, 2008). Furthermore, the IC 50 value in cancer cell was 2-4 fold less than that in normal cells, thus conjugates in the same dose could lead to distinctive cytotoxicity in different cell lines, demonstrating that PEI-CyD-tegafur was relatively protective to normal cells and toxic to cancer cells.…”
Section: Discussionmentioning
confidence: 61%
“…Polymeric drug delivery systems (Arias et al, 2007;2008a;2008b;Zeng et al, 2009) and chemicallysynthesized derivatives (Stokes et al, 2002;Zhang et al, 2007;Engel et al, 2008) can perform controlled release of tegafur upon exposure to specific conditions and thus improve anti-cancer activity. Compared to those prodrugs mentioned above, polyethylenimine-cyclodextrin (PEI-CyD) copolymer has not only the ability to deliver drugs (Zhao et al, 2009) as well as plasmid DNA (Tang et al, 2006) but also the potential to perform co-delivery of genes and anti-cancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Typical structures such as aspidosperma alkaloid (-)-aspidophytine [ 4 , 5 ], lycopodium alkaloid lycoplanine A [ 6 ], indoline alkaloid rosibiline [ 7 ], and macrocyclic marine alkaloid ‘upenamide [ 8 , 9 ] are shown in Figure 1 . Besides, Tegafur [ 10 ] containing a hemiaminal ether skeleton is used as an anticancer reagent and indolinooxzolidines [ 11 ] are effective in molecular switching.…”
Section: Introductionmentioning
confidence: 99%